Genetic parameters for lifetime productivity in Holstein and Brown Swiss dairy cows in Honduras - Karen Alessa Copas-Medina; Manuel Valladares-Rodas; Juan José Baeza-Rodríguez; José Candelario Segura-Correa; Juan Magaña-Monforte (Revista MVZ Cordoba)
Objective. To estimate the heritability (h2) of age at first parturition (AFP), longevity (L), useful life (UL), and productivity (P), as well as the genetic (rg) and phenotypic correlations between those traits in Brown Swiss and Holstein cows in Northwestern Honduras. Materials and methods. Cattle were raised under tropical conditions and intensive management. The model for AFP assessed the effect of contemporary group (herd, year and birth season combination) as fixed. The model used for L, UL and P included the contemporary group, age group at first calving and their interaction. Data were analyzed using restricted maximum likelihood procedure, adjusted to a univariate and to a bivariate animal model. Results. The h2 estimated for AFP, L, UL and P were 0.16, 0.18, 0.25 and 0.09, respectively, in Brown Swiss cows, and 0.53, 0.49, 0.7 and 0.22, respectively in Holstein. Negative but favorable rg among Brown Swiss cow traits ranged from 0.31 to 0.46 between AFP and the other traits. However, for Holsteins cows, positive rg among AFP and the other traits here studied varied from 0.49 to 0.96. In both cattle breeds, rg among L, UL and P, traits were positive. Conclusions. For all traits evaluated low to medium heritability’s for BS suggest that a slow genetic improvement could be achieved if independent selection of traits is applied, and better response could be expected for H breed. For both breeds the positive rg among L, UL and P suggest thar similar selection criteria could be used.